2010
DOI: 10.1111/j.1420-9101.2010.02192.x
|View full text |Cite
|
Sign up to set email alerts
|

Horizontally acquired DAP pathway as a unit of self-regulation

Abstract: In this study, we report the acquisition of the diaminopimelic acid (DAP) pathway of lysine biosynthesis in choanoflagellate Monosiga brevicollis and investigate how this pathway is incorporated and regulated in the established metabolic network. Our data show that all major genes related to the DAP pathway in Monosiga were acquired from bacteria and algae. Although an endogenous lysC exists in Monosiga, the newly acquired lysC is fused to lysA and used specifically for lysine biosynthesis. In addition, these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 56 publications
(127 reference statements)
2
18
0
Order By: Relevance
“…We categorized the remaining 193 genes according to their putative biological functions (Figure 3). About one third of them (32.1%, 62 genes) are related to carbohydrate metabolism, 28 of which were also identified in earlier analyses [15, 16, 31, 49] and 34 are newly reported in this study (Additional file 1). Because of the importance of carbohydrates as basic energy sources and structural components, carbohydrate metabolism is interwoven with multiple other biochemical processes.…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…We categorized the remaining 193 genes according to their putative biological functions (Figure 3). About one third of them (32.1%, 62 genes) are related to carbohydrate metabolism, 28 of which were also identified in earlier analyses [15, 16, 31, 49] and 34 are newly reported in this study (Additional file 1). Because of the importance of carbohydrates as basic energy sources and structural components, carbohydrate metabolism is interwoven with multiple other biochemical processes.…”
Section: Resultssupporting
confidence: 72%
“…Interestingly, after comparing with our previous studies [31] and unpublished data, we found that 17 genes were absent from the candidate lists predicted by all three programs. Three of these genes were identified when we studied the evolutionary history of the branched aspartate-derived pathway [31]; 14 other genes were identified when we performed analyses on other candidates. Most of these missed genes have an alien index score (bit score ratio between the top hit from distantly related taxa and that from closely related taxa) less than 1.2, which is the default setting of AlienG.…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…Yue et al (2013) have calculated that 4.4% of the Monosiga brevicollis genome derives from LGT, one of the highest rates reported for unicellular eukaryotes to date. The phosphofructokinase gene from Monosiga ovata may have originated in spirochetes (Bapteste et al 2003) and pathways for amino acid biosynthesis in M. brevicollis also seem to have been acquired from bacteria (Torruella et al 2009;Sun and Huang 2011). Intriguingly, M. brevicollis also appears to carry…”
Section: Implications Of a History Of Bacterivory On The Genetic Toolmentioning
confidence: 99%